Internal migration and the health of Indigenous Mexicans: A longitudinal study - Gabriela León-Pérez (SSM: Population Health, 2019)
Rationale: Indigenous peoples have historically comprised a substantial part of migration streams around the world, yet our understanding of the effects of migration on indigenous health is limited. Objective: To explore the migration-indigenous health relationship by assessing the impact of internal migration on the self-rated health trajectories of indigenous Mexicans. Data and method: Using three waves of data (2002–2012) from the Mexican Family Life Survey, I estimated linear growth curves to examine differences in initial self-rated health and changes in self-rated health between indigenous and non-indigenous respondents (N = 12,533). Then, I investigated whether migrating domestically during the study period shaped indigenous health trajectories. Results: At the baseline interview (before migration), indigenous migrants reported significantly better self-rated health than indigenous non-migrants and than all non-indigenous respondents. In spite of their better initial health, indigenous migrants’ health deteriorated substantially after migration, such that by the time of the last interview they reported the worst health. The self-rated health of all other groups improved during the same period. Conclusion: Findings provide evidence of pre-migration health selection and post-migration health deterioration among Mexican indigenous migrants. These results suggest that internal migration is a risk factor that has an independent effect on indigenous health even after adjusting for personal, family, socioeconomic, and health care factors. Keywords: Mexico, Indigenous health, Internal migration, Self-rated health, Healthy migrant hypothesis